SUC-CORE: A Balanced Corpus Annotated with Noun Phrase Coreference - Kristina Nilsson Björkenstam (Northern European Journal of Language Technology)
This paper describes SUC-CORE, a subset of the Stockholm Ume°a Corpus and the Swedish Treebank annotated with noun phrase coreference. While most coreference annotated corpora consist of exts of similar types within related domains, SUC-CORE consists of both informative and imaginative prose and covers a wide range of literary genres and domains. This allows for exploration of coreference cross different text types, but it also means that there are limited amounts of data within each type. Future work on coreference resolution for Swedish should include making more annotated data vailable for the research community.